(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
This study investigated correlation among availability, utilisation of textbooks and students’ achievement in chemistry in Senior Secondary Schools in AMAC, Abuja. The study adopted the descriptive research design of the correlational type. Ten public secondary schools were randomly selected from public secondary schools in AMAC, Abuja. Simple random sampling technique was used to select 30 SS II students from each school, making a total of 300 SS II students. In all, 300 SS II students participated in the study. Three research instruments were used for data collection: Questionnaire on Text Availability (r=.76), Questionnaire on Text Utilisation (r=.78) and Achievement Test in Chemistry (r=.87). Data collected were analysed using Pearson Product Moment Correlation and Multiple Regression Analysis. Findings of the study revealed that text availability had a negative relationship with students’ achievement in chemistry (r = -.065), text utilisation had a positive relationship with students’ achievement in chemistry (r = .091). The joint contribution of text availability and utilisation to students’ achievement in chemistry was not significant (F (2; 297) = 2.469; Adj. R2 = .010; p>0.05). Also, text utilisation (β = .114) had more relative contribution to students’ achievement in chemistry than text availability (β = -.093). Based on the findings, it was recommended that students who wish to excel in chemistry, must be ready to utilise all the recommended texts. Ministry of Education and external examination bodies should try to always recommend chemistry textbooks whose approach is simple and that can easily be understood by students. Teachers of chemistry should encourage students to read the prescribed textbooks and ensure that students read all the recommended textbooks.